Coping Strategies for Physically Challenged Children - Abraham, Bindu Kaipparettu (International Journal of Innovative Research in Medical Science, 2018)
The aim of this research is to assess the coping strategies of physically challenged children. The area of assessment included in physical, emotional and social problems related to their physical disability. Descriptive research design was selected to study the physical, emotional and social problems and its coping strategies of physically challenged children. Purposive sampling technique used for 50 samples of Physically challenged children between the age group of 10-15 years who were educated at the special school in Mangalore. It was reached from the result of the findings that physically challenged children are using negative coping mechanism for social problems related to their physical disability whereas physical and emotional problems related to physical disability most of them are using positive coping mechanism.